1982
DOI: 10.1042/bj2060597
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of [LeuB-24]- and [LeuB-25]-insulin analogues. Receptor binding and biological activity

Abstract: Human [LeuB-24]- and [LeuB-25]-insulins were semi-synthesized from porcine insulin by an enzyme-assisted coupling method. The receptor-binding ability of [LeuB-24]- and [LeuB-25]-insulins was 30--48% and 2--5% respectively of that of human insulin. There was no significant difference in degradation between human insulin and these analogues on incubation with isolated adipocytes. The decreased affinity of these analogues was due to an increased dissociation rate rather than a change in the association rate of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(30 citation statements)
references
References 20 publications
3
27
0
Order By: Relevance
“…1 (18) and that immunometric equivalency must be separately assessed for each new or uncommon insulin analogue under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…1 (18) and that immunometric equivalency must be separately assessed for each new or uncommon insulin analogue under investigation.…”
Section: Methodsmentioning
confidence: 99%
“…Vertebrate insulin sequences exhibit broad conservation (17), including several invariant residues recently shown to pack at the primary hormone-receptor interface (4) (13,(55)(56)(57). Co-evolution of the hormone-receptor interface has presumably led to the strict conservation of such contact sites.…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes internalize membrane-associated insulin and this internalization results in the degradation of the hormone (2)(3)(4)(5)(6)(7)(8) or the receptor (25,26). The degradation occurs at a chloroquine-sensitive location (6-8, 25, 26) and therefore, it has been presumed that adipocyte lysosomes accumulate and degrade This study showed that chloroquine had no effects on the initial binding of insulin to its receptor, on the distribution of insulin receptors on the cell surface, or on the initial phases of the uptake process.…”
Section: Discussionmentioning
confidence: 99%
“…An increased accumulation of intact insulin in adipocytes has been reported when lysosome function was inhibited by chloroquine (6-8); quantitative biochemical analyses of the insulin uptake process in adipocytes have estimated that about 15-30% of the receptorbound hormone was internalized (6-8) and approximately 25-50% ofthe internalized hormone was degraded at a chloroquinesensitive site (5, 9). In a number ofstudies chloroquine-sensitive insulin degradation was found to be a small percentage of the total insulin-degradative activity of adipocytes (6)(7)(8)10).Several laboratories have used morphological techniques to study the binding and uptake of insulin (for a review, see ref.11). We have found that monomeric ferritin-labeled insulin initially occupied receptor sites on the adipocyte plasma membrane and was endocytosed in pinocytotic invaginations and transported to cytoplasmic vesicles (unpublished data).…”
mentioning
confidence: 99%
See 1 more Smart Citation